2012
DOI: 10.1097/sla.0b013e3182658180
|View full text |Cite
|
Sign up to set email alerts
|

Admission Rapid Thrombelastography Can Replace Conventional Coagulation Tests in the Emergency Department

Abstract: The r-TEG data was clinically superior to results from 5 CCTs. In addition, r-TEG identified patients with an increased risk of early RBC, plasma and platelet transfusions, and fibrinolysis. Admission CCTs can be replaced with r-TEG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
309
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 366 publications
(319 citation statements)
references
References 73 publications
3
309
2
5
Order By: Relevance
“…Prothrombin time, partial thromboplastin time, and international normalized ratio are not used on admission because they have been shown to be of little value and TEG provides more rapid and useful data. 12 Cryoprecipitate is used when the maximal amplitude is Ͻ 55, and venous thromboembolism prophylaxis is escalated when the maximal amplitude is Ͼ 65. 13 Tranexamic acid is used when the LY-30 is Ն 3% on the admission TEG.…”
mentioning
confidence: 99%
“…Prothrombin time, partial thromboplastin time, and international normalized ratio are not used on admission because they have been shown to be of little value and TEG provides more rapid and useful data. 12 Cryoprecipitate is used when the maximal amplitude is Ͻ 55, and venous thromboembolism prophylaxis is escalated when the maximal amplitude is Ͼ 65. 13 Tranexamic acid is used when the LY-30 is Ն 3% on the admission TEG.…”
mentioning
confidence: 99%
“…Cotton et al and Holcomb et al demonstrated that the r-TEG values for activated clotting time (ACT), k-time, and the R-time were available within 5 minutes, and the maximal amplitude (mA) and alpha angle were available within 15 minutes. These values correlated with CCTs in relation to coagulopathy [16,21]. To date, few reports have described the utility of r-TEG in diagnosing coagulopathy in TBI patients.…”
Section: Introductionmentioning
confidence: 66%
“…Coagulopathy was defined by the presence of one or more of the following: aPTT >35 seconds, INR >1.5, platelet count <150 x 10 9 /L, fibrinogen <180 mg/dL, ACT >128 seconds, k >2.5 minutes, alpha <56 degrees, mA <55 millimeters, and LY30 >3% (21). These critical TEG values were based on our previous work where inflection points on scatter-plot analyses identified when transfusion requirements and mortality increased substantially.…”
Section: Definitions and Outcomesmentioning
confidence: 99%
“…In a prospective cohort study of 517 trauma patients, thromboelastography enabled rapid detection of hypofi brinogenemia, and early administration of fi brinogen was related with improved survival [23]. Using rapid thromboelastography, Holcomb et al re cently succeeded in identifying patients with an increased risk of fi brinolysis and erythrocyte, plasma and platelet transfusions out of 1,974 major trauma patients [24]. Schochl et al [25] retrospectively analyzed the eff ects of thromboelastometry-guided hemostatic therapy in 131 trauma patients who received ≥ 5 erythrocyte concentrate units within 24 hours after admission.…”
Section: Massive Bleeding and Trauma Patientsmentioning
confidence: 99%